What is the radicate Oudemansiella cultivated in China? - Hao, Yan-Jia; Zhao, Qi; Wang, Shou-Xian; Yang, Zhu L. (Phytotaxa, 2016)
A radicate Oudemansiella species, called “Heipijizong” or “Black Termite Mushroom”, has been widely cultivated in China in the past few years. It was regarded as either the European O. radicata or the North American O. furfuracea or even species of Termitomyces. This study aims to clarify the taxonomic position of this economically important mushroom. Phylogenetic analyses of “Heipijizong” and other related Oudemansiella species were carried out using ITS and nrLSU ribosomal RNA gene regions. Based on both morphological and molecular data, “Heipijizong” was identified as Oudemansiella raphanipes. Our study indicated that O. raphanipes possesses both 2-spored and 4-spored basidiomata. Detailed morphological descriptions and illustrations are provided for it.